2012
DOI: 10.1038/srep00250
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone responsive neural precursor cells reside within the adult mammalian brain

Abstract: The detection of growth hormone (GH) and its receptor in germinal regions of the mammalian brain prompted our investigation of GH and its role in the regulation of endogenous neural precursor cell activity. Here we report that the addition of exogenous GH significantly increased the expansion rate in long-term neurosphere cultures derived from wild-type mice, while neurospheres derived from GH null mice exhibited a reduced expansion rate. We also detected a doubling in the frequency of large (i.e. stem cell-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…In agreement with a more recent [88,89] . Growth hormone (GH) has also been shown in vitro to increase proliferation of neurosphere-derived NPCs by acting directly through the GH receptor [90,91] . In uninjured mice, GH increased NPC proliferation in the SVZ and olfactory bulb when delivered intraventricularly.…”
Section: Proliferationmentioning
confidence: 99%
“…In agreement with a more recent [88,89] . Growth hormone (GH) has also been shown in vitro to increase proliferation of neurosphere-derived NPCs by acting directly through the GH receptor [90,91] . In uninjured mice, GH increased NPC proliferation in the SVZ and olfactory bulb when delivered intraventricularly.…”
Section: Proliferationmentioning
confidence: 99%
“…The presence of GH receptors in neural stem cells suggests the ability of GH to regulate their activities 34 . Blackmore and his colleagues showed that a seven-day intracerebroventricular infusion of GH increases neural stem cell numbers and augments neurogenesis activity in vitro 35 . Furthermore, GH treatment promotes the proliferation and survival of hippocampal progenitors 21 .…”
Section: Discussionmentioning
confidence: 99%
“…These two brain areas express GHR mRNA (Bennett et al 1996, Minami et al 2006 in different cells types including astrocytes (Lobie et al 1993, Blackmore et al 2012. GRLN-R1a is also located in both the CNS and the periphery (Zigman et al 2006).…”
Section: Discussionmentioning
confidence: 99%